Ventral striatum and amygdala activity as convergence sites for early adversity and conduct disorder - Holz, Nathalie E. (Soc Cogn Affect Neurosci, 2016)
Childhood family adversity (CFA) increases the risk for conduct disorder (CD) and has been associated with alterations in regions of affective processing like ventral striatum (VS) and amygdala. However, no study so far has demonstrated neural converging effects of CFA and CD in the same sample. At age 25 years, functional MRI data during two affective tasks, i.e. a reward (N = 171) and a face-matching paradigm (N = 181) and anatomical scans (N = 181) were acquired in right-handed currently healthy participants of an epidemiological study followed since birth. CFA during childhood was determined using a standardized parent interview. Disruptive behaviors and CD diagnoses during childhood and adolescence were obtained by diagnostic interview (2–19 years), temperamental reward dependence was assessed by questionnaire (15 and 19 years). CFA predicted increased CD and amygdala volume. Both exposure to CFA and CD were associated with a decreased VS response during reward anticipation and blunted amygdala activity during face-matching. CD mediated the effect of CFA on brain activity. Temperamental reward dependence was negatively correlated with CFA and CD and positively with VS activity. These findings underline the detrimental effects of CFA on the offspring's affective processing and support the importance of early postnatal intervention programs aiming to reduce childhood adversity factors.